Suplementasi Antioksidan pada Maturasi In Vitro Menurunkan Kadar ROS: A Literature Review - Amalia Ratna Kusumaningrum (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
One of the reproductive health problems is infertility. In vitro maturation (IVM) is emerging as a popular technology at the forefront of fertility treatment. IVM conditions inducing a series of events related to reactive oxygen species (ROS), which have been implicated as one of the major causes for reduced embryonic development. Therefore, the supplementation of IVM media with antioxidants could improve the survival and development of the oocytes. The method of searching conducted online database such as Science Direct, Sage, Pubmed, Springer, and Oxford. The keywords that used were “antioxidant”, “reactive oxygen species”, “in vitro maturation”, “infertility” and “assisted reproductive technology”. The literatures restricted in 2008 year until 2019 in English. The results of the study show that there were 3 main themes, types, dosages, antioxidant benefits for reduced ROS levels during IVM. The drawback that might arise in this study is that there are still possibilities of not getting some related articles. The literature review is expected to be a basis for research assisted reproductive technology. Keywords: antioxidant; in vitro maturation; infertility; Reactive oxygen species (ROS)